2022
DOI: 10.1017/s0007123422000175
|View full text |Cite
|
Sign up to set email alerts
|

Public Demand for Extraterritorial Environmental and Social Public Goods Provision

Abstract: Vastly increased transnational business activity in recent decades has been accompanied by controversy over how to cope with its social and environmental impacts. The most prominent policy response thus far consists of international guidelines. We investigate to what extent and why citizens in a high-income country are willing to restrain companies to improve environmental and social conditions in other countries. Exploiting a real-world referendum in Switzerland, we use choice and vignette experiments with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 106 publications
1
4
0
Order By: Relevance
“…On the one hand, our results indicate that deontologist preferences could be an overlooked aspect of public opinion on foreign policy making, at least whenever deadly force is in question. On the other hand, our arguments and results are associated with recent findings in related areas where (domestic) economic benefits, security and normative considerations interact (albeit to varying degrees) – for example, decisions on military interventions (Dill & Schubiger, 2021; Tomz & Weeks, 2020), provision of foreign aid (Heinrich et al., 2018), international trade (Lechner, 2016) or foreign direct investment (Rudolph, Kolcava, et al., 2023).…”
Section: Introductionsupporting
confidence: 76%
“…On the one hand, our results indicate that deontologist preferences could be an overlooked aspect of public opinion on foreign policy making, at least whenever deadly force is in question. On the other hand, our arguments and results are associated with recent findings in related areas where (domestic) economic benefits, security and normative considerations interact (albeit to varying degrees) – for example, decisions on military interventions (Dill & Schubiger, 2021; Tomz & Weeks, 2020), provision of foreign aid (Heinrich et al., 2018), international trade (Lechner, 2016) or foreign direct investment (Rudolph, Kolcava, et al., 2023).…”
Section: Introductionsupporting
confidence: 76%
“…Moreover, we contribute to recent research investigating how non-material interests shape the preferences of individuals on public goods provision. Recent research has focused on other-regarding concerns/preferences (Rudolph, Kolcava and Bernauer 2022;Bechtel, Genovese and Scheve 2019). Our paper indicates that perceived costs can have important non-material elements as well, in our case perceptions of health risks (in addition to material costs (Rho and Tomz 2017)).…”
Section: Discussionmentioning
confidence: 70%
“…This decrease could be a consequence of the economic shock driven by sociotropic considerations of citizens (Beiser-McGrath 2022), but might be due to time confounding, also. Future research could investigate the role of such sociotropic considerations, which have been found to matter in related areas such as trade policy (Schaffer and Spilker 2019) or sustainable supply chains (Rudolph, Kolcava, and Bernauer 2022).…”
Section: Discussionmentioning
confidence: 99%